Primerjava izbranih funkcij informacijskih sistemov Scopus in Web of Science - Bartol, Tomaž (Knjižnica, 2012)
Acquisition of information resources in Slovenia is directed through the Slovenian Research Agency (ARRS). Web of Science (WoS) has been accessible for many years. Scopus Trial has only become available during the last year. Comparison of both databases focuses on functional characteristics. Principal current functions of both search systems are assessed (as of the second half of the year 2011). Search possibilities are compared e.g. (Document) Search based on the selection of fields from pulldown menus, and Advanced Search, requiring the application of search-operators. Limits, arrangement of records (Sort by), and advanced analytics (Analyze/Refine) areevaluated, with some emphasize on citations (Cited Reference Search). The new WoS interface (essentially) retains the previous arrangement of tasks, adding some novel functions and possibilities. Lemmatization can be turned off. Cited-reference-search in WoS remains easy, it is principally based on the author search, with the authority control for author-sets, however, still somehow weak. Unique author sets are frequently hard to define. Scopus offers complex search possibilities for a very high number of fields, including the All Fields search, and the Reference title search. Unique authors seem to be grouped together more consistently in Scopus. However, the same authors can stili come about in different sets. Also, stemming (lemmatizati on) can not be turned off in Scopus. This analysis as well as the review of literature, substantiate the need for concurrent use of both databases, in order to obtain optimal search results. Nevertheless, the complexity of both information systems requires advanced information competency of end-users.
Keywords: informacijska znanost; prenos informacij; informacijski viri; podatkovne zbirke; ovrednotenje; iskalne značilnosti; iskalni vmesniki; citiranje